Malaria Outbreak investigation in Chitulipasi, Beitbridge District, Matebeleland South Province, 2015 - Chiruvu, Roy Tapiwa; Kanengoni, Blessing; Mungati, More; Gombe, Notion Tafara; Bangure, Donewell; Tshimanga, Mufuta; Mhlanga, Maxwell (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Background: Cases of Malaria at Chitulipasi clinic in Ward One of Beitbridge district surpassedepidemic thresholds from week 9 through week 15. In total 223 cases were recorded in ward onefrom weeks 9 to 15. We investigated the outbreak of malaria in Ward One.Methods: A one on one unmatched case control study was conducted among residents in WardOne. A case was a person from Ward One who presented to Chitulipasi clinic with sudden onsetof intermittent fever associated with any of the following; shivering, sweating, joint and musclepains, nausea, vomiting, diarrhoea and headache and was diagnosed malaria with RapidDiagnostic Testing, from weeks 7 to 15 of 2015. Sixty cases and 60 controls were systematicallyand randomly selected respectively. Written informed consent was obtained from all studyparticipants. Data were analysed using Epi Info.Results: Females constituted 53.3% (n=32) and 55.0% (n=33) of cases and controls respectively(p=0.86). The median ages in years were 22 (Q1=13; Q3=37) and 23 (Q1=17; Q3=35) for casesand controls respectively (p=0.95). Staying in house with closed eaves (OR 0.05 95% CI 0.01,0.40), staying 3km away from stagnant water body (OR 0.30 95% CI 0.13, 0.70) and having anet hanging per sleeping space (OR 0.07 95% CI 0.03, 0.17) were significant protective factorsfor contracting malaria.Conclusion: The outbreak was driven by staying near stagnant water, staying in houses withopen eaves and not using a mosquito net. Emphasis on larviciding, utilization of nets andsleeping under nets should be made. Health education was provided to the community.